Jejunal lysozyme activity and the Paneth cell in coeliac disease. Issue 1 (January 1979) - Ward, M; Ferguson, A; Eastwood, M A
Abstract : The jejunal mucosa of patients with coeliac disease contains significantly fewer Paneth cells (PCC) per crypt (p less than 0.001) and tissue lysozyme activity (JLA) P less than 0.001) when compared with a group of subjects with normal jejunal mucosa. Neither PCC nor JLA return to normal with complete clinical recovery and otherwise complete histological recovery on a gluten free diet. There is a significant linear correlation between JLA and PCC suggesting that the Paneth cell is the principal source of jejunal lysozyme.